2012
DOI: 10.1007/s00421-012-2564-9
|View full text |Cite
|
Sign up to set email alerts
|

Endurance training modifies exercise-induced activation of blood coagulation: RCT

Abstract: Randomized controlled trials (RCTs) on the topic of physical training and blood coagulation are rare and the effects are unclear. The aim of this study was to investigate whether endurance training adjusts blood coagulation and fibrinolysis at rest and after exercise. The study included 50 healthy untrained non-smokers randomized into training (TR 49 ± 6 years) or control group (CO 48 ± 6 years). Each subject performed an exercise test adjusted at 80 % individual anaerobic threshold (IAT) for 60 min before and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 30 publications
5
30
1
Order By: Relevance
“…This was not confirmed in the present study, where no effects on ETP were observed after 3 and 6 months of active commuting or moderate- or vigorous-intensity leisure-time exercise 4-5 times/week. To our knowledge, only Hilberg et al have previously investigated the effects of physical training on fasting levels of ETP in healthy adults, and similar to the present study, they reported no effects of 12 weeks of vigorous-intensity exercise on men who are overweight and who exercised with a frequency of 3-4 times/week [24]. …”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…This was not confirmed in the present study, where no effects on ETP were observed after 3 and 6 months of active commuting or moderate- or vigorous-intensity leisure-time exercise 4-5 times/week. To our knowledge, only Hilberg et al have previously investigated the effects of physical training on fasting levels of ETP in healthy adults, and similar to the present study, they reported no effects of 12 weeks of vigorous-intensity exercise on men who are overweight and who exercised with a frequency of 3-4 times/week [24]. …”
Section: Discussionsupporting
confidence: 81%
“…Acute exercise is known to activate coagulation and fibrinolytic properties [22, 24, 4547], and the findings of the present study, along with the findings by Hilberg et al [24], may suggest that less-frequent activation of coagulation through ∼4 exercise sessions/week for 3 or 6 months does not lower ETP levels in overweight individuals. We speculate that high-frequency (daily) acute exercise with coagulation activation might consume coagulation factors and thereby reduce ETP.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The beneficial effect of aerobic exercise in accelerating the metabolic rate and burn fat, fight obesity and increase blood circulation leading to transfer larger amount of oxygen and nutrients to the muscles has already be proven by research (Hilberg et al, 2013;Mikus et al, 2011;Sand et al, 2013). The increase in aerobic physical activity is now considered a key component of lifestyle modification in order to prevent and treat high blood pressure (Whelton et al, 2002).…”
Section: Introductionmentioning
confidence: 99%